A Comparison of Outcomes After Lower Extremity Bypass and Repeat Endovascular Intervention Following Failed Previous Endovascular Intervention for Critical Limb Ischemia. (July 2019) - Shannon, Alexander H.; Mehaffey, J. Hunter; Cullen, J. Michael; Upchurch, Gilbert R.; Robinson, William P.
The optimal approach for repeat revascularization after failed endovascular intervention for critical limb ischemia (CLI) is unclear. This study compared major adverse limb events (MALEs) and major adverse cardiac events (MACEs) between lower extremity bypass (LEB) and repeat endovascular intervention (REI) in patients with prior failed ipsilateral endovascular intervention. American College of Surgeons National Surgical Quality Improvement Program database identified patients undergoing LEB and endovascular intervention for CLI from 2011 to 2014. We compared REI to LEB with single-segment saphenous vein (LEB-SV) and LEB alternative conduit (LEB-alt). Primary outcomes were 30-day MALE and MACE. Multivariate analysis identified independent predictors of MALE and MACE. A total of 1567 revascularizations were performed after failed ipsilateral endovascular intervention (REI: 683 [43.5%], LEB-SV: 570 [36.4%], LEB-alt: 314 [20.0%]). There were 994 and 573 suprageniculate and infrageniculate revascularizations, respectively. Major adverse cardiac events were significantly lower after REI compared to LEB (REI: 15 [2.2%], LEB-SV: 33 [5.8%], LEB-alt: 21 [6.7%], P < .001). Major adverse limb event were not different between groups ( P = .99). In patients with CLI presenting after failed endovascular intervention, REI is associated with lower MACE without an increased risk of MALE compared to LEB. When the anatomy is amenable, REI should be considered a less morbid first option.